Molecular functionalization of silicene/Ag(111) by covalent bonds: a DFT study. Issue 22 (14th June 2015) - Stephan, Régis; Hanf, Marie-Christine; Sonnet, Philippe
<x xml:space="preserve">Abstract</x> Thanks to differential functional theory calculations, we show that a benzene molecule can be chemisorbed in the butterfly configuration on the (3 × 3) silicene/(4 × 4) Ag(111) surface by means of two Si–C covalent bonds.